Optimization of Preparation of Activated Carbon from Ricinus communis Leaves by Microwave-Assisted Zinc Chloride Chemical Activation: Competitive Adsorption of Ni2+ Ions from Aqueous Solution - M. Makeswari; T. Santhi (Journal of Chemistry)
The preparation of activated carbon (AC) from Ricinus communis leaves was investigated in this paper. Orthogonal array experimental design method was used to optimize the preparation of AC using microwave assisted zinc chloride. Optimized parameters were radiation power of 100 W, radiation time of 8 min, concentration of zinc chloride of 30% by volume, and impregnation time of 24 h, respectively. The surface characteristics of the AC prepared under optimized conditions were examined by pHZPC, SEM-EDAX, XRD, and FTIR. Competitive adsorption of Ni2+ ions on Ricinus communis leaves by microwave assisted zinc chloride chemical activation (ZLRC) present in binary and ternary mixture was compared with the single metal solution. The effects of the presence of one metal ion on the adsorption of the other metal ion were investigated. The experimental results indicated that the uptake capacity of one metal ion was reduced by the presence of the other metal ion. The extent of adsorption capacity of the binary and ternary metal ions tested on ZLRC was low (48–69%) as compared to single metal ions. Comparisons with the biosorption of Ni2+ ions by the biomass of ZLRC in the binary (48.98–68.41%-~Ni-Cu and 69.76–66.29%-~Ni-Cr) and ternary solution (67.32–57.07%-~Ni–Cu and Cr) could lead to the conclusion that biosorption of Ni2+ ions was reduced by the influence of Cu2+ and Cr3+ ions. The equilibrium data of the adsorption was well fitted to the Langmuir isotherm. The adsorption process follows the pseudo-second-order kinetic model.